Kocca Lanjheng as a Sign of Honor: Symbolic Communication of Blater's Social Identity in Madura Society (Literasi Nusantara, 2025)
This study examines the role of Kocca Lanjheng as a symbol of honor and social identity within Madurese society, particularly in relation to the social figure of Blater in Bangkalan. Using a qualitative ethnographic–semiotic approach, the research explores how Kocca Lanjheng is interpreted, practiced, and negotiated through everyday social interactions. Data were collected through participant observation, in-depth interviews, and documentation. The findings indicate that Kocca Lanjheng functions as a contemporary cultural symbol embodying values of honor, firmness, courage, and social legitimacy. Although relatively recent, its acceptance is rooted in long-standing Madurese principles of dignity and collective recognition. The study concludes that Kocca Lanjheng operates as a dynamic symbolic system bridging tradition and modernity, reinforcing collective identity and shaping social relations in Madurese society.
Keywords: Kocca Lanjheng; Blater; Cultural Symbols; Social Identity; Madura